2005
DOI: 10.1177/135965350601100309
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Preferences regarding the Timing of Highly Active Antiretroviral Therapy Initiation for Chronic Asymptomatic HIV-1 Infection

Abstract: Objective In patients with a chronic asymptomatic HIV-1 infection and >200 CD4+ T-cells/μl, the optimal timing of highly active antiretroviral therapy (HAART) initiation is unclear. It involves a trade-off between a potentially reduced risk of mortality, when started earlier in the course of infection, and an earlier exposure to pill burden and potential toxicities. We investigated patients’ preferences for immediate HAART initiation relative to delaying HAART for 1 year. Methods Consecutive patients were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Because the standard gamble procedure involves comparisons of probabilities that can be confusing to participants, psychological and behavioral economic studies of health preferences have relied almost exclusively on variations ofthe TTO method (e.g., Chapman, 2002;Locadia et al, 2006). The TTO method assesses the length of time in good health that participants consider equivalent to a period of time in bad health, typically followed by death.…”
Section: Methods Used To Study Health-related Decisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the standard gamble procedure involves comparisons of probabilities that can be confusing to participants, psychological and behavioral economic studies of health preferences have relied almost exclusively on variations ofthe TTO method (e.g., Chapman, 2002;Locadia et al, 2006). The TTO method assesses the length of time in good health that participants consider equivalent to a period of time in bad health, typically followed by death.…”
Section: Methods Used To Study Health-related Decisionsmentioning
confidence: 99%
“…In a study of preferences for nonfatal health outcomes over three delay intervals (2-5, 6-9, and 10-13 years), 67% of participants had positive time perspectives, and the rest had zero or negative time preferences (van der Pol & Cairns, 2000). Another study showed that a sizable minority of HIV-positive patients wanted to start highly active antiretroviral therapy earlier than recommended by treatment guidelines, even though it often has severe side effects (Locadia et al, 2006). Negative time preferences have also been associated with accepting flu shots and perceiving health outcomes as more serious, whereas positive time preferences have been associated with older age (Chapman et al, 2001;Shleinitz, DePalo, Blume, & Stein, 2006).…”
Section: Negative Time Preferencesmentioning
confidence: 99%
“…32,37,38,[75][76][77]80,[83][84][85][86]91,92,94,95,97 However, not expectantly, previous experience of side effects was associated with patients becoming more risk averse. 64,[101][102][103][104][105][106][107][108] A model depicting the inter-relationship and dynamic impact of disease severity, disease duration and treatment experience on patients' preferences and risk tolerance in chronic disease is represented in Figure 2.…”
Section: Narrative Synthesismentioning
confidence: 99%